Induction of adaptive response in E. coli cells alkylating agents depend on their chemical structure (Eurasian Journal of Ecology, 2023)
The most well–known alkylating agents (AA) used in mutational breeding of agricultural crops and microorganisms producing biologically active substances are methyl methanesulfonate (MMS) and ethylmethanesulfone (EMS). It is known that both of these substances effectively induce bacterial alkyltransferase, which leads to an adaptive response of bacteria, that is, to the development of resistance to toxic effects. Bacterial alkyltransferase is a homologue of O6-methylguanine-DNA-methyltransferase in human cells. The study of the induction of alkyltransferase in bacteria by various AA allows us to predict their ability to induce an adaptive response in human cells. Lux biosensors pColDp-lux and pAlkA-lux were used to study the ability of MMS, ECG and BPL to induce DNA damage and adaptive response in E.coli cells. MMS effectively elicited an SOS response in the ColD-lux biosensor, characterizing the level of DNA damage, and an adaptive response recorded in the AlkA-lux biosensor by inducing the expression of the alkyltransferase gene. Bifunctional ECG induced both SOS response and adaptive response less actively than monofunctional MMS. The BPL induced an SOS response only at low concentrations, and did not cause an adaptive response at the same concentrations. Thus, bifunctional ECG and BPL, whose activity depends on the reactivity of the products of the disclosure of their cyclic structures, alkylate DNA to a lesser extent than MMC. This is due to the fact that they form electrophilic methyl groups to a lesser extent than MMCs when the cycle is opened.Keywords: lux-biosensor, E.coli, SOS response, adaptive response, methyl methanesulfonate, epichlorohydrin, beta-propiolactone.